Nursing students' use of social media in their learning: a case study of a Canadian School of Nursing - Catherine M. Giroux; Katherine A. Moreau (BMC, 2022)
Abstract Background Social media has diverse applications for nursing education. Current literature focuses on how nursing faculty use social media in their courses and teaching; less is known about how and why nursing students use social media in support of their learning. Objectives The purpose of this study was to explore how nursing students use social media in their learning formally and informally. Methods This exploratory qualitative case study of a Canadian School of Nursing reports on the findings of interviews (n = 9) with nursing students to explore how they use social media in their learning. Data were analyzed using a combined deductive and inductive coding approach, using three cycles of coding to facilitate category identification. Results and conclusions The findings demonstrate that participants use social media for formal and informal learning and specifically, as a third space to support their learning outside of formal institutional structures. Social media plays a role in the learning activities of nursing students studying both face-to-face and by distance. Accordingly, social media use has implications for learning theory and course design, particularly regarding creating space for student learning communities.